Reducing High-Users' Visits to the Emergency Department by a Primary Care Intervention for the Uninsured: A Retrospective Study. (27th March 2018) - Tsai, Meng-Han; Xirasagar, Sudha; Carroll, Scott; Bryan, Charles S.; Gallagher, Pamela J.; Davis, Kim; Jauch, Edward C.
Reducing avoidable emergency department (ED) visits is an important health system goal. This is a retrospective cohort study of the impact of a primary care intervention including an in-hospital, free, adult clinic for poor uninsured patients on ED visit rates and emergency severity at a nonprofit hospital. We studied adult ED visits during August 16, 2009-August 15, 2011 (preintervention) and August 16, 2011-August 15, 2014 (postintervention). We compared pre- versus post-mean annual visit rates and discharge emergency severity index (ESI; triage and resource use–based, calculated Agency for Healthcare Research and Quality categories) among high-users (≥3 ED visits in 12 months) and occasional users. Annual adult ED visit volumes were 16 372 preintervention (47.5% by high-users), versus 18 496 postintervention. High-users' mean annual visit rates were 5.43 (top quartile) and 0.94 (bottom quartile) preintervention, versus 3.21 and 1.11, respectively, for returning high-users, postintervention (all P < .001). Postintervention, the visit rates of new high-users were lower (lowest and top quartile rates, 0.6 and 3.23) than preintervention high-users' rates in the preintervention period. Visit rates of the top quartile of occasional users also declined. Subgroup analysis of medically uninsured high-users showed similar results. Upon classifying preintervention high-users by emergency severity, postintervention mean ESI increased 24.5% among the lowest ESI quartile, and decreased 12.2% among the top quartile. Pre- and post-intervention sample demographics and comorbidities were similar. The observed reductions in overall ED visit rates, particularly low-severity visits; highest reductions observed among high-users and the top quartile of occasional users; and the pattern of changes in emergency severity support a positive impact of the primary care intervention.